Recurrent congenital diaphragmatic hernia: A single center experience - Żaneta Słowik-Moczydłowska; Andrzej Kamiński (PAGEPress Publications, 2021)
Congenital Diaphragmatic Hernia (CDH) occurs in 1:4000 live births. It's morbidity and mortality rates are significant. Recurrence is one of the recognized complications occurring after a successful initial repair. Poorly known are the rate of recurrence and factors that may influence the re-herniation. Poorly described are its morphology and treatment. Medical records of 95 neonates with CDH who had undergone repair at tertiary pediatric teaching hospital between 2007-2018 were retrospectively reviewed. Prior to surgery, peri-operative and recurrence data were collected. The follow-up was 1 to 12 years after the initial repair. Recurrence occurred in 22/84 (26%) patients. In 5 patients we observed more than one recurrence, total number of 27 (32%) re-herniations; 16/22 (72%) recurrences occurred within first 12 months; 7/27 (26%) recurrences were symptomatic which gives the symptomatic recurrence rate 8.3%; 20/27 (74%) were asymptomatic. There were no significant differences between groups considering LHR, gestational age, birth weight, severity of pre-surgery and post-surgery stabilization period. Significantly higher Apgar scores were in the group without recurrence. Among subjects with recurrent CDH majority had a left-sided defect, no hernia sac, no liver herniation, diaphragm was primarily sutured, abdominal wall primarily closed. Even though none of those factors was significantly related with the recurrence. Recurrence in CDH remains a significant issue for long-term surgical morbidity, especially more apparent in the first year of life. As long as the risk factors of re-herniation remains unclear, the most important seems to be routine follow-up protocol allowing for CDH recurrence detection.